2017
DOI: 10.18632/oncotarget.14811
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid inhibits the proliferation of human pancreatic carcinoma PANC-1 cells in vitro and in vivo

Abstract: Ellagic aicd (EA), a dietary polyphenolic compound found in plants and fruits, possesses various pharmacological activities. This study investigated the effect of EA on human pancreatic carcinoma PANC-1 cells both in vitro and in vivo; and defined the associated molecular mechanisms. In vitro, the cell growth and repairing ability were assessed by CCK-8 assay and wound healing assay. The cell migration and invasion activity was evaluated by Tanswell assay. In vivo, PANC-1 cell tumor-bearing mice were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…The smallest ellagitannin, 2,3-hexahydroxydiphenoylglucose, is defined from the condensation of single HHDP and glucose subunits (482.070 Da) but whether to include species with molecular weights lower than this when reporting ellagitannins has not yet been standardized 62 , 68 . A targeted mass exclusion list was initially considered to ensure no singly charged m/z below 481.062 would be included for precursor selection, but was not added to the method parameters given general interest and precedent set by recent studies 62 , 69 72 . Species below 482.070 Da were omitted from T-2RT enumeration (Table 2 ) to accurately report ellagitannin summary values in addition to the aforementioned adjustments for charge state and isotope duplicates.…”
Section: Resultsmentioning
confidence: 99%
“…The smallest ellagitannin, 2,3-hexahydroxydiphenoylglucose, is defined from the condensation of single HHDP and glucose subunits (482.070 Da) but whether to include species with molecular weights lower than this when reporting ellagitannins has not yet been standardized 62 , 68 . A targeted mass exclusion list was initially considered to ensure no singly charged m/z below 481.062 would be included for precursor selection, but was not added to the method parameters given general interest and precedent set by recent studies 62 , 69 72 . Species below 482.070 Da were omitted from T-2RT enumeration (Table 2 ) to accurately report ellagitannin summary values in addition to the aforementioned adjustments for charge state and isotope duplicates.…”
Section: Resultsmentioning
confidence: 99%
“…Ellagic acid also seems to inhibit the growth, ability to repair, migration, and invasion of human pancreatic carcinoma PANC-1 cells in a dose dependent manner. Thus, PANC-1 cell tumor-bearing mice treated with ellagic acid had an increased survival rate, with inhibition of tumor growth through cell cycle arrest in the G 1 phase; downregulation of COX-2, NF-κB, and vimentin; and upregulation of E-cadherin [188].…”
Section: Cytotoxic Antitumor and Anticancer Effects Of Ellagic Acidmentioning
confidence: 97%
“…Ellagitannins are hydrolyzed in the gut to release ellagic acid (EA), a compound which inhibits multiple oncogenic pathways which are activated in PDAC such as COX-2, NF-kB, Notch, and Wnt signaling. Preclinical studies have shown that targeted blockade of these pathways by EA is successful in reducing epithelial-mesenchymal transition, angiogenesis, fibrosis, and pancreatic stellate cell activation in PDAC (8,9). Despite these promising developments, EA is unfortunately poorly absorbed within the human gut, limiting its efficacy as a therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Uro A has been shown to downregulate multiple tumor pathways in colon, prostate, and bladder cancer through downregulation of several oncogenes such as Kras and c-myc, upregulation of tumor-suppressor genes such as FGFR2 and EGFR, and modulation of enzyme activity, such as CYP1 (13). Despite the promising effects seen in treating other malignancies, the anticancer effect of Uro A in PDAC is currently unknown (8,9).…”
Section: Introductionmentioning
confidence: 99%